(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The stellar purpose of the present study is to know how far the moderator variables impact the study on digitalisation in banking industry. Further, the study also intended to know the before and after digitalisation effect, the challenges faced and benefits of digitalisation in the banking industry in Bengaluru. The traditional relationship between bank and its customer is one-to-one (Bhagyashree, 2018) but the modern outlook of banks with customers is one-to-many. The digital product helps the banks to provide their performance and also helps to widen market and improve financial position and performance. Approach: A structured closed ended questionnaire was administered as schedule in order to avoid delay, incompleteness and rejection. Respondents were approached for the purpose of data collection by meeting the respondents in the banks premises. The respondents were interviewed in a natural setting and requested to provide data. x2, Kendall’s coefficient of concordance, weighted arithmetic mean and Garrett Ranking technique was performed. Findings: The study found the presence of significant variation in the data and with high degree of relationship. Kendall’s coefficient of concordance reveals that after digitalisation the respondents getting more benefits. Further, the benefits emerged from the research includes creates more convenience to the customers, the second rank was awarded to creates prerequisite and favourable conditions for successful development of virtual enterprises and third rank was given to two equal variables rural and urban gap is eliminated and number of customers will be amplified. The challenges include cybercrime, increasing competition and creating valuable content.